1998
DOI: 10.1152/ajpcell.1998.274.2.c347
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic regulation of endothelial glyceraldehyde-3-phosphate dehydrogenase

Abstract: The glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is induced by hypoxia in endothelial cells (EC). To define the mechanisms by which GAPDH is regulated by hypoxia, EC were exposed to cobalt, other transition metals, carbon monoxide (CO), deferoxamine, or cycloheximide in the presence or absence of hypoxia for 24 h, and GAPDH protein and mRNA levels were measured. GAPDH was induced in cells by the transition metals cobalt, nickel, and manganese and by deferoxamine, and GAPDH mRNA induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 35 publications
12
103
0
Order By: Relevance
“…To analyze transcriptional control, run-off transcription assays were performed that showed a 2.7-fold up-regulation of VPF/VEGF mRNA transcription by hypoxia in M21 cells compared with the 36B4 control, which was unaffected (Figure 2A). In comparison, GAPDH showed a 3-fold and Glut-1 a 2.5-fold transcription up-regulation, consistent with the increased hypoxic expression of both of these genes (Graven et al, 1994;Ebert et al, 1995). The level of increased gene transcription, however, only partially accounted for the total increase in VPF/VEGF mRNA expression observed by Northern blot analysis, suggesting an additional effect of hypoxia on mRNA stability.…”
Section: Hypoxia-induced Vpf/vegf Mrna Expression In M21 Melanoma Celsupporting
confidence: 68%
“…To analyze transcriptional control, run-off transcription assays were performed that showed a 2.7-fold up-regulation of VPF/VEGF mRNA transcription by hypoxia in M21 cells compared with the 36B4 control, which was unaffected (Figure 2A). In comparison, GAPDH showed a 3-fold and Glut-1 a 2.5-fold transcription up-regulation, consistent with the increased hypoxic expression of both of these genes (Graven et al, 1994;Ebert et al, 1995). The level of increased gene transcription, however, only partially accounted for the total increase in VPF/VEGF mRNA expression observed by Northern blot analysis, suggesting an additional effect of hypoxia on mRNA stability.…”
Section: Hypoxia-induced Vpf/vegf Mrna Expression In M21 Melanoma Celsupporting
confidence: 68%
“…The reference gene selection was addressed in our studies as it is reported that hypoxia is able to alter the expression of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), 37 which has been commonly used as a reference gene in many chondrocyte quantitative PCR analyses. A reference gene selection study was therefore performed.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the discrepancy of our data with other studies might be the use of GAPDH as a reference gene in the quantitative RT-PCR assay. GAPDH was demonstrated as one of several genes which are up-regulated in breast ductal carcinoma compared to histologically normal tissue (Bini et al, 1997) and a significant correlation of VEGF mRNA and GAPDH mRNA expression was found in breast carcinomas (Scott et al, 1998b), possibly because both genes are regulated by hypoxia (Graven et al, 1998). Potentially, an increased number of VEGF mRNA transcripts parallel to an up-regulation of GAPDH in carcinomatous tissue might have caused the similar VEGF/GAPDH ratios in malignant and benign breast tissue allowing only separate comparisons in our study for benign and malignant tissue (Figure 2).…”
Section: Discussionmentioning
confidence: 99%